Medical nutrition therapy for gestational diabetes mellitus based on Mediterranean Diet principles: a subanalysis of the St Carlos GDM Prevention Study. Issue 1 (11th October 2018) - Assaf-Balut, Carla; Garcia de la Torre, Nuria; Durán, Alejandra; Fuentes, Manuel; Bordiú, Elena; del Valle, Laura; Valerio, Johanna; Familiar, Cristina; Jiménez, Inés; Herraiz, Miguel Angel; Izquierdo, Nuria; Torrejón, Maria José; et al.
Abstract : Objectives: To assess whether Mediterranean Diet (MedDiet)-based medical nutrition therapy facilitates near-normoglycemia in women with gestational diabetes mellitus (GDMw) and observe the effects on adverse pregnancy outcomes. Research design and methods: This is a secondary analysis of the St Carlos GDM Prevention Study, conducted between January and December 2015 in Hospital Clínico San Carlos (Madrid, Spain). One thousand consecutive women with normoglycemia were included before 12 gestational weeks (GWs), with 874 included in the final analysis. Of these, 177 women were diagnosed with gestational diabetes mellitus (GDM) and 697 had normal glucose tolerance. All GDMw received MedDiet-based medical nutrition therapy with a recommended daily extra virgin olive oil intake ≥40 mL and a daily handful of nuts. The primary goal was comparison of hemoglobin A1c (HbA1c ) levels at 36–38 GWs in GDMw and women with normal glucose tolerance (NGTw). Results: GDMw as compared with NGTw had higher HbA1c levels at 24–28 GWs (5.1%±0.3% (32±0.9 mmol/mol) vs 4.9%±0.3% (30±0.9 mmol/mol), p=0.001). At 36–38 GWs values were similar between the groups. Similarly, fasting serum insulin and homeostatic model assessment insulin resitance (HOMA-IR) were higher in GDMw at 24–28 GWs (p=0.001) but became similar at 36–38 GWs. 26.6% of GDMw required insulin for glycemic control. GDMw compared with NGTw had higher rates of insufficient weight gain (39.5% vs 22.0%, p=0.001), small for gestational age (6.8% vs 2.6%, p=0.009), and neonatal intensive care unit admission (5.6% vs 1.7%, p=0.006). The rates of macrosomia, large for gestational age, pregnancy-induced hypertensive disorders, prematurity and cesarean sections were comparable with NGTw. Conclusions: Using a MedDiet-based medical nutrition therapy as part of GDM management is associated with achievement of near-normoglycemia, subsequently making most pregnancy outcomes similar to those of NGTw.